Perceptual Benefits of Extended Bandwidth Hearing Aids With Children: A Within-Subject Design Using Clinically Available Hearing Aids - Van Eeckhoutte, Maaike; Scollie, Susan; O'Hagan, Robin; Glista, Danielle (Journal of speech, language, and hearing research, 2020)
Purpose: The aim of the study was to investigate the achieved audibility with clinically available, modern, high-end, behind-the-ear hearing aids fitted using the Desired Sensation Level v5.0 child prescription for a clinical sample of children with hearing impairment and the effect of the extended bandwidth provided by the hearing aids on several outcome measures. Method: The achieved audibility was measured using the maximum audible output frequency method. Twenty-eight children (7-17 years old) with mild to severe hearing losses completed this study. Two hearing aid conditions were fitted for each participant: an extended bandwidth condition, which was fitted to targets as closely as possible, and a restricted bandwidth condition, for which aided output was restricted above 4.5 kHz. Consonant discrimination in noise, subjective preference, aided loudness growth, and preferred listening levels were evaluated in both conditions. Results: The extended bandwidth hearing aid fittings provided speech audibility above 4.5 kHz for all children, with an average maximum audible output frequency of 7376 Hz (SD = 1669 Hz). When compared to a restricted bandwidth, the extended bandwidth condition led to an improvement of 5.4% for consonant discrimination in noise scores, mostly attributable to /s/, /z/, and /t/ phoneme perception. Aided loudness results and preferred listening levels were not significantly different across bandwidth conditions; however, 65% of the children indicated a subjective preference for the extended bandwidth. Conclusion: The study suggests that providing the full bandwidth available, with modern, behind-the-ear hearing aids, leads to improved audibility, when compared to restricted bandwidth hearing aids, and that it leads to beneficial outcomes for children who use hearing aids, fitted to the Desired Sensation Level v5.0 child prescription, without causing significant increases in their loudness perception.